Exposure to High Aerial Ammonia Causes Hindgut Dysbiotic Microbiota and Alterations of Microbiota-Derived Metabolites in Growing Pigs - Tang, Shanlong; Zhong, Ruqing; Yin, Chang; Su, Dan; Xie, Jingjing; Chen, Liang; Liu, Lei; Zhang, Hongfu (Frontiers in Nutrition, 2021)
Ammonia, an atmospheric pollutant in the air, jeopardizes immune function, and perturbs metabolism, especially lipid metabolism, in human and animals. The roles of intestinal microbiota and its metabolites in maintaining or regulating immune function and metabolism are irreplaceable. Therefore, this study aimed to investigate how aerial ammonia exposure influences hindgut microbiota and its metabolites in a pig model. Twelve growing pigs were treated with or without aerial ammonia (35 mg/m3) for 25 days, and then microbial diversity and microbiota-derived metabolites were measured. The results demonstrated a decreasing trend in leptin (p = 0.0898) and reduced high-density lipoprotein cholesterol (HDL-C, p = 0.0006) in serum after ammonia exposure. Besides, an upward trend in hyocholic acid (HCA), lithocholic acid (LCA), hyodeoxycholic acid (HDCA) (p < 0.1); a downward trend in tauro-deoxycholic acid (TDCA, p < 0.1); and a reduced tauro-HDCA (THDCA, p < 0.05) level were found in the serum bile acid (BA) profiles after ammonia exposure. Ammonia exposure notably raised microbial alpha-diversity with higher Sobs, Shannon, or ACE index in the cecum or colon and the Chao index in the cecum (p < 0.05) and clearly exhibited a distinct microbial cluster in hindgut indicated by principal coordinate analysis (p < 0.01), indicating that ammonia exposure induced alterations of microbial community structure and composition in the hindgut. Further analysis displayed that ammonia exposure increased the number of potentially harmful bacteria, such as Negativibacillus, Alloprevotella, or Lachnospira, and decreased the number of beneficial bacteria, such as Akkermansia or Clostridium_sensu_stricto_1, in the hindgut (FDR < 0.05). Analysis of microbiota-derived metabolites in the hindgut showed that ammonia exposure increased acetate and decreased isobutyrate or isovalerate in the cecum or colon, respectively (p < 0.05). Unlike the alteration of serum BA profiles, cecal BA data showed that high ammonia exposure had a downward trend in cholic acid (CA), HCA, and LCA (p < 0.1); a downward trend in deoxycholic acid (DCA) and HDCA (p < 0.05); and an upward trend in glycol-chenodeoxycholic acid (GCDCA, p < 0.05). Mantel test and correlation analysis revealed associations between microbiota-derived metabolites and ammonia exposure-responsive cecal bacteria. Collectively, the findings illustrated that high ammonia exposure induced the dysbiotic microbiota in the hindgut, thereby affecting the production of microbiota-derived short-chain fatty acids and BAs, which play a pivotal role in the modulation of host systematic metabolism.